Penguatan Identitas Usaha Melalui Logo Guna Meningkatkan Visual Branding UMKM di Kejawan Putih Tambak - Atik Novita; Takarini, Nurjanti (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This service was carried out with the aim of overcoming the main challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Kejawan Putih Tambak, namely the lack of a strong brand identity and knowledge of attractive visual content. The main focus of the community service program was on the role of visual branding in increasing the competitiveness of MSMEs in the digital era, where logos as the main element of identity can help products become more recognizable to consumers and expand market reach. By strengthening business identity through logos, it is hoped that in the future, business actors can establish a strong brand image, enabling MSMEs to compete more effectively. The community service program consisted of three stages, namely preparation, implementation, and evaluation. The results of this community service show a significant increase in business actors' understanding of business logos. Before the socialization, business actors still had minimal knowledge about the importance of having a business identity, which resulted in a low level of business logo ownership of only 18% of MSMEs. However, after the socialization, the understanding of business actors increased dramatically, so that now 66% of MSMEs in Kejawan Putih Tambak have business logos. These results confirm that assistance to MSMEs is necessary in driving local economic growth through effective branding strategies, which ultimately contribute to the sustainability of MSMEs amid increasingly fierce market competition. Abstrak: Pengandian ini dilakukan dengan tujuan ini untuk mengatasi tantangan utama yang dihadapi oleh Usaha Mikro, Kecil, dan Menengah (UMKM) di Kejawan Putih Tambak, yaitu kurangnya identitas merek yang kuat serta pengetahuan mengenai konten visual yang menarik. Fokus utama pengabdian terletak pada peran visual branding dalam meningkatkan daya saing UMKM di era digital, dimana logo sebagai elemen identitas utama dapat membantu produk lebih dikenali konsumen dan memperluas jangkauan pasar. Melalui penguatan identitas usaha melalui logo diharapkan kedepanya pelaku usaha dapat membentuk citra merek yang kuat, sehingga UMKM dapat bersaing lebih efektif. Metode pengabdian terdiri dari tiga tahap yakni persiapan, pelaksanaan, dan evaluasi. Hasil pengabdian ini menunjukkan adanya peningkatan yang signifikan dalam pemahaman pelaku usaha mengenai logo usaha. Sebelum sosialisasi, pelaku usaha masih minim akan pengetahuan akan pentingnya memiliki identitas usaha yang berdampak pada rendahnya tingkat kepemilikan logo usaha yang hanya sebesar 18% UMKM, namun setelah diadakan sosialisasi, pemahaman pelaku usaha meningkat drastis, sehingga kini 66% UMKM di Kejawan Putih Tambak telah memiliki logo usaha.